2017
DOI: 10.5348/ijbti-2017-28-oa-1
|View full text |Cite
|
Sign up to set email alerts
|

Hepcidin testing; establishing reference values for the Namibian blood donor population

Abstract: Aims: Anemia is a global health concern affecting billions of people worldwide. The diagnostic approach to iron deficiency anemia could be streamlined in an attempt to increase diagnostic sensitivity and to reduce uncertainties in interpreting laboratory generated results. In doing so the introduction of hepcidin testing may prove to be useful but this requires the establishment of reference normal ranges. The main aim of this study was to establish reference values of hepcidin in the Namibian blood donor popu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“… 29 Similarly, reference range of 17.186 to 91.237 ng/mL for Namibian female blood donor population and 29 to 254 ng/mL was observed by previous studies. 30 Galesloot et al also established normal ranges for hepcidin in the Netherlands with median of 4.1 nM. 21 …”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“… 29 Similarly, reference range of 17.186 to 91.237 ng/mL for Namibian female blood donor population and 29 to 254 ng/mL was observed by previous studies. 30 Galesloot et al also established normal ranges for hepcidin in the Netherlands with median of 4.1 nM. 21 …”
Section: Discussionmentioning
confidence: 98%
“…29 Similarly, reference range of 17.186 to 91.237 ng/mL for Namibian female blood donor population and 29 to 254 ng/mL was observed by previous studies. 30 Galesloot et al also established normal ranges for hepcidin in the Netherlands with median of 4.1 nM. 21 Hepcidin is master regulator of iron homeostasis through its effect on ferroportin; therefore, it gives an accurate estimate of iron bioavailability.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unique nature of health resource allocation approaches, the standard treatment guidelines tend to be country specific. Some treatment interventions and diagnostic tests such as hepcidin levels may not be available 11 …”
Section: Discussionmentioning
confidence: 99%
“…The study showed that the patients who are routinely screened for IDA include symptomatic adults (70.6%), pregnant patients (68.8%), all patients during general medical check‐up (60.8%) and symptomatic children (58.8%). It is generally expected that pregnant women are screened for IDA as they are more vulnerable to IDA due to increased demands of iron by the growing foetus 11 . Screening all patients during general medical check‐up is ideal because some asymptomatic IDA cases may be identified sooner more so in pregnancy 13…”
Section: Discussionmentioning
confidence: 99%